(untitled) (Research, Society and Development, 2022)
This essay aims to discuss the method and data analysis used by Vygotsky in his research based on Historical-Dialectical Materialism, which makes a unique contribution to the understanding of phenomena and how they fit into reality. Taking as theoretical support the ideas of Vygotsky and his theoretical articulation with Marx, when he chooses the centrality of work as the foundation of the social being and origin of the human psyche, thus enabling important contributions to Historical-Cultural Psychology. This article seeks to contribute to the understanding of the scientific rigor used in the research developed by Vygotsky, who based his theoretical-methodological perspective on the close relationship between psychology and philosophy. The Russian psychologist showed in his works a care with the research method, he was a deep connoisseur of the science and history of psychology, he managed to contribute to the construction of a new investigative method to understand the psychological functions. In this way, Vygotsky considered important the description of the phenomena that reveals their external aspect, the phenotype, but he looked for a deeper understanding of the issue by saying that it is completed with the understanding of its internal aspect, of its genotype. The author based his studies on the historical-dialectical materialist method that preys on the search for the totality of the researched object. Finally, we understand that working with a research based on Historical-Cultural Psychology referenced in Historical-Dialectical Materialism consists of a concern to understand the investigated phenomenon, describing and looking for its possible relationships, integrating the individual with the cultural in the search for totality.